# Question and Answers Forum

Integration Questions

Question Number 151421 by peter frank last updated on 21/Aug/21

$$\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} \mathrm{log}\:\left(\mathrm{1}+\mathrm{tan}\:\mathrm{x}\right)\mathrm{dx} \\$$

Commented bypuissant last updated on 21/Aug/21

$${x}=\frac{\pi}{\mathrm{4}}−{t}\:\rightarrow\:{dx}=−{dt} \\$$ $${Q}=\int_{\frac{\pi}{\mathrm{4}}} ^{\mathrm{0}} {ln}\left(\mathrm{1}+{tan}\left(\frac{\pi}{\mathrm{4}}−{t}\right)\right)\left(−{dt}\right) \\$$ $$=\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} {ln}\left(\mathrm{1}+\frac{\mathrm{1}−{tant}}{\mathrm{1}+{tant}}\right){dt} \\$$ $$=\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} {ln}\left(\frac{\mathrm{1}+{tant}}{\mathrm{1}+{tant}}+\frac{\mathrm{1}−{tant}}{\mathrm{1}+{tant}}\right){dt} \\$$ $$\Rightarrow\:{Q}=\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} {ln}\left(\frac{\mathrm{2}}{\mathrm{1}+{tant}}\right){dt} \\$$ $$\Rightarrow\:{Q}=\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} {ln}\mathrm{2}{dx}−\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} {ln}\left(\mathrm{1}+{tant}\right){dt} \\$$ $$\Rightarrow\:\mathrm{2}{Q}=\frac{\pi}{\mathrm{4}}{ln}\mathrm{2} \\$$ $$\:\:\:\:\:\:\:\:\:\:\because\therefore\:\:{Q}=\frac{\pi}{\mathrm{8}}{ln}\mathrm{2}... \\$$

Commented bypeter frank last updated on 21/Aug/21

$$\mathrm{thank}\:\mathrm{you} \\$$

Answered by peter frank last updated on 21/Aug/21

$$\mathrm{x}=\frac{\pi}{\mathrm{4}}−\theta \\$$ $$\mathrm{dx}=−\mathrm{d}\theta \\$$ $$\left(\mathrm{0},\frac{\pi}{\mathrm{4}}\right)\Leftrightarrow\left(\frac{\pi}{\mathrm{4}},\mathrm{0}\right) \\$$ $$\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} \mathrm{log}\:\left[\mathrm{1}+\mathrm{tan}\:\left(\frac{\pi}{\mathrm{4}}−\theta\right)\right]\mathrm{d}\theta \\$$ $$\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} \mathrm{log}\:\left[\mathrm{1}+\frac{\mathrm{tan}\:\frac{\pi}{\mathrm{4}}−\mathrm{tan}\:\theta}{\mathrm{1}+\mathrm{tan}\:\frac{\pi}{\mathrm{4}}\mathrm{tan}\:\theta}\right] \\$$ $$\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} \mathrm{log}\left[\:\frac{\mathrm{2}}{\mathrm{1}+\mathrm{tan}\:\theta}\right]\mathrm{d}\theta \\$$ $$\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} \mathrm{log}\:\mathrm{2d}\theta−\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} \mathrm{log}\:\left(\mathrm{1}+\mathrm{tan}\:\theta\right) \\$$ $$\mathrm{2I}=\mathrm{log}\:\mathrm{2}\left[\theta\right]_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} \\$$ $$\mathrm{I}=\frac{\pi}{\mathrm{8}}\mathrm{log}\:\mathrm{2} \\$$ $$\\$$

Answered by mathmax by abdo last updated on 21/Aug/21

$$\mathrm{f}\left(\mathrm{a}\right)=\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} \mathrm{log}\left(\mathrm{1}+\mathrm{atanx}\right)\mathrm{dx}\:\:\:\:\:\left(\mathrm{a}>\mathrm{0}\right)\:\Rightarrow \\$$ $$\mathrm{f}^{'} \left(\mathrm{a}\right)=\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} \frac{\mathrm{tanx}}{\mathrm{1}+\mathrm{atanx}}=\frac{\mathrm{1}}{\mathrm{a}}\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} \:\frac{\mathrm{1}+\mathrm{atanx}−\mathrm{1}}{\mathrm{1}+\mathrm{atanx}}\mathrm{dx} \\$$ $$=\frac{\pi}{\mathrm{4a}}−\frac{\mathrm{1}}{\mathrm{a}}\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} \:\frac{\mathrm{dx}}{\mathrm{1}+\mathrm{atanx}}\:\left[\mathrm{we}\:\mathrm{have}\right. \\$$ $$\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} \:\frac{\mathrm{dx}}{\mathrm{1}+\mathrm{atanx}}\:=_{\mathrm{tanx}=\mathrm{t}} \:\:\int_{\mathrm{0}} ^{\mathrm{1}\:} \:\frac{\mathrm{dt}}{\left(\mathrm{1}+\mathrm{t}^{\mathrm{2}} \right)\left(\mathrm{1}+\mathrm{at}\right)} \\$$ $$\mathrm{F}\left(\mathrm{t}\right)=\frac{\mathrm{1}}{\left(\mathrm{at}+\mathrm{1}\right)\left(\mathrm{t}^{\mathrm{2}} \:+\mathrm{1}\right)}=\frac{\alpha}{\mathrm{at}+\mathrm{1}}+\frac{\mathrm{mt}+\mathrm{n}}{\mathrm{t}^{\mathrm{2}} \:+\mathrm{1}} \\$$ $$\alpha=\frac{\mathrm{1}}{\frac{\mathrm{1}}{\mathrm{a}^{\mathrm{2}} }+\mathrm{1}}=\frac{\mathrm{a}^{\mathrm{2}} }{\mathrm{1}+\mathrm{a}^{\mathrm{2}} } \\$$ $$\mathrm{lim}_{\mathrm{t}\rightarrow+\infty} \mathrm{tF}\left(\mathrm{t}\right)=\frac{\alpha}{\mathrm{a}}\:+\mathrm{m}\:\Rightarrow\mathrm{m}=−\frac{\alpha}{\mathrm{a}}=−\frac{\mathrm{a}}{\mathrm{1}+\mathrm{a}^{\mathrm{2}} } \\$$ $$\Rightarrow\mathrm{F}\left(\mathrm{t}\right)=\frac{\mathrm{a}^{\mathrm{2}} }{\left(\mathrm{1}+\mathrm{a}^{\mathrm{2}} \right)\left(\mathrm{at}+\mathrm{1}\right)}+\frac{−\frac{\mathrm{a}}{\mathrm{1}+\mathrm{a}^{\mathrm{2}} }\mathrm{t}\:+\mathrm{n}}{\mathrm{t}^{\mathrm{2}} \:+\mathrm{1}} \\$$ $$\mathrm{F}\left(\mathrm{0}\right)=\frac{\mathrm{a}^{\mathrm{2}} }{\mathrm{1}+\mathrm{a}^{\mathrm{2}} }\:+\mathrm{n}=\mathrm{1}\:\Rightarrow\mathrm{n}=\mathrm{1}−\frac{\mathrm{a}^{\mathrm{2}} }{\mathrm{1}+\mathrm{a}^{\mathrm{2}} }=\frac{\mathrm{1}}{\mathrm{1}+\mathrm{a}^{\mathrm{2}} }\:\Rightarrow \\$$ $$\mathrm{F}\left(\mathrm{t}\right)=\frac{\mathrm{a}^{\mathrm{2}} }{\left(\mathrm{a}^{\mathrm{2}} \:+\mathrm{1}\right)\left(\mathrm{at}+\mathrm{1}\right)}+\frac{−\frac{\mathrm{a}}{\mathrm{a}^{\mathrm{2}} \:+\mathrm{1}}\mathrm{t}+\frac{\mathrm{1}}{\mathrm{1}+\mathrm{a}^{\mathrm{2}} }}{\mathrm{t}^{\mathrm{2}} \:+\mathrm{1}} \\$$ $$\Rightarrow\int_{\mathrm{0}} ^{\mathrm{1}} \:\mathrm{F}\left(\mathrm{t}\right)\mathrm{dt}=\frac{\mathrm{a}^{\mathrm{2}} }{\left(\mathrm{a}^{\mathrm{2}} \:+\mathrm{1}\right)}\int_{\mathrm{0}} ^{\mathrm{1}} \:\frac{\mathrm{dt}}{\mathrm{at}+\mathrm{1}}−\frac{\mathrm{1}}{\mathrm{a}^{\mathrm{2}} \:+\mathrm{1}}\int_{\mathrm{0}} ^{\mathrm{1}\:} \frac{\mathrm{at}−\mathrm{1}}{\mathrm{t}^{\mathrm{2}} \:+\mathrm{1}}\mathrm{dt} \\$$ $$=\frac{\mathrm{a}}{\mathrm{a}^{\mathrm{2}} \:+\mathrm{1}}\left[\mathrm{ln}\left(\mathrm{at}+\mathrm{1}\right)\right]_{\mathrm{0}} ^{\mathrm{1}} −\frac{\mathrm{a}}{\mathrm{2}\left(\mathrm{a}^{\mathrm{2}} \:+\mathrm{1}\right)}\left[\mathrm{ln}\left(\mathrm{t}^{\mathrm{2}} \:+\mathrm{1}\right)\right]_{\mathrm{0}} ^{\mathrm{1}} \:+\frac{\mathrm{1}}{\mathrm{a}^{\mathrm{2}} \:+\mathrm{1}}\frac{\pi}{\mathrm{4}} \\$$ $$=\frac{\mathrm{aln}\left(\mathrm{1}+\mathrm{a}\right)}{\mathrm{a}^{\mathrm{2}} \:+\mathrm{1}}−\frac{\mathrm{ln2}}{\mathrm{2}}×\frac{\mathrm{a}}{\mathrm{a}^{\mathrm{2}} +\mathrm{1}}\:+\frac{\pi}{\mathrm{4}\left(\mathrm{a}^{\mathrm{2}} \:+\mathrm{1}\right)}\:\Rightarrow \\$$ $$\mathrm{f}^{'} \left(\mathrm{a}\right)=\frac{\pi}{\mathrm{4a}}−\frac{\mathrm{ln}\left(\mathrm{1}+\mathrm{a}\right)}{\mathrm{a}^{\mathrm{2}} \:+\mathrm{1}}+\frac{\mathrm{ln2}}{\mathrm{2}\left(\mathrm{a}^{\mathrm{2}\:} +\mathrm{1}\right)}\:−\frac{\pi}{\mathrm{4a}\left(\mathrm{a}^{\mathrm{2}} \:+\mathrm{1}\right)} \\$$ $$\mathrm{f}\left(\mathrm{1}\right)=\mathrm{f}\left(\mathrm{1}\right)−\mathrm{f}\left(\mathrm{0}\right)=\int_{\mathrm{0}} ^{\mathrm{1}} \:\mathrm{f}^{'} \left(\mathrm{a}\right)\mathrm{da}=\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} \mathrm{log}\left(\mathrm{1}+\mathrm{tant}\right)\mathrm{dt} \\$$ $$=\int_{\mathrm{0}} ^{\mathrm{1}} \frac{\pi}{\mathrm{4a}}\left(\mathrm{1}−\frac{\mathrm{1}}{\mathrm{a}^{\mathrm{2}} \:+\mathrm{1}}\right)\mathrm{da}−\int_{\mathrm{0}} ^{\mathrm{1}} \:\frac{\mathrm{ln}\left(\mathrm{1}+\mathrm{a}\right)}{\mathrm{a}^{\mathrm{2}} \:+\mathrm{1}}\mathrm{da}+\frac{\mathrm{ln2}}{\mathrm{2}}\int_{\mathrm{0}} ^{\mathrm{1}} \:\frac{\mathrm{da}}{\mathrm{1}+\mathrm{a}^{\mathrm{2}} } \\$$ $$=\frac{\pi}{\mathrm{4}}\int_{\mathrm{0}} ^{\mathrm{1}} \frac{\mathrm{a}}{\mathrm{a}^{\mathrm{2}} \:+\mathrm{1}}\mathrm{da}−\int_{\mathrm{0}} ^{\mathrm{1}} \:\frac{\mathrm{ln}\left(\mathrm{1}+\mathrm{a}\right)}{\mathrm{1}+\mathrm{a}^{\mathrm{2}} }\mathrm{da}+\frac{\pi}{\mathrm{4}}×\frac{\mathrm{ln2}}{\mathrm{2}} \\$$ $$=\frac{\pi}{\mathrm{8}}\left[\mathrm{ln}\left(\mathrm{a}^{\mathrm{2}} +\mathrm{1}\right)\right]_{\mathrm{0}} ^{\mathrm{1}} +\frac{\pi\mathrm{ln2}}{\mathrm{8}}−\int_{\mathrm{0}} ^{\mathrm{1}} \:\frac{\mathrm{ln}\left(\mathrm{1}+\mathrm{a}\right)}{\mathrm{1}+\mathrm{a}^{\mathrm{2}} }\mathrm{da}\:\left(\mathrm{a}=\mathrm{tan}\theta\right) \\$$ $$=\frac{\pi\mathrm{ln}\left(\mathrm{2}\right)}{\mathrm{8}}+\frac{\pi\mathrm{ln2}}{\mathrm{8}}−\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} \:\frac{\mathrm{ln}\left(\mathrm{1}+\mathrm{tan}\theta\right)}{\mathrm{1}+\mathrm{tan}^{\mathrm{2}} \theta}\left(\mathrm{1}+\mathrm{tan}^{\mathrm{2}} \theta\right)\mathrm{d}\theta \\$$ $$=\frac{\pi\mathrm{ln2}}{\mathrm{4}}−\mathrm{I}\:\Rightarrow\mathrm{2I}=\frac{\pi\mathrm{ln2}}{\mathrm{4}}\:\Rightarrow\mathrm{I}=\frac{\pi}{\mathrm{8}}\mathrm{ln}\left(\mathrm{2}\right)\:\Rightarrow \\$$ $$\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} \mathrm{ln}\left(\mathrm{1}+\mathrm{tan}\theta\right)\mathrm{d}\theta=\frac{\pi}{\mathrm{8}}\mathrm{ln}\left(\mathrm{2}\right) \\$$

Commented bypeter frank last updated on 21/Aug/21

$$\mathrm{thank}\:\mathrm{you} \\$$